Performance of the jet transport airplane : analysis methods, flight operations, and regulations - Young, Trevor M. (Aerospace series (Chichester, England), 2018)
Presenting a detailed and comprehensive treatment of performance analysis techniques for jet transport airplanes, this unique book describes key operational and regulatory procedures and constraints that directly impact the performance of commercial airliners. --